What happens to drug use and expenditure when cost sharing is completely removed? Evidence from a Canadian provincial public drug plan. Issue 9 (September 2020) - Laba, Tracey-Lea; Cheng, Lucy; Worthington, Heather C.; McGrail, Kimberlyn M.; Chan, Fiona K.I.; Mamdani, Muhammad; Law, Michael R.
Highlights: Completely removing drug cost-sharing increased drug use (16%) and expenditure (19%). Much change was attributable to new users of medicines, especially systemic anti-infectives. The appropriateness of this additional medication use requires investigation. Abstract: Objectives: The role of cost-sharing for medicines is under active policy discussion, including in proposals for value-based insurance design. To inform this debate, we estimated the impact of completely removing cost-sharing on medication use and expenditure using a quasi-experimental approach. Methods: Fair PharmaCare, British Columbia's income-based public drug plan, includes a household out-of-pocket limit. Therefore, when one household member starts a long-term high-cost drug surpassing this maximum, cost-sharing is completely removed for other family members. We used an interrupted time series design to estimate monthly prescriptions and expenditures of other household members, 24 months before and after cost-sharing removal. Results: We studied 2191 household members newly free of cost-sharing requirements, most of whom had lower incomes. R emoving cost-sharing increased the level of drug expenditure and prescription numbers by 16 and 19%, respectively (i.e. $2659.43 (95%$1507.27–$3811.59, p < 0.001); 50.0 (95%CI 25.1–74.9, p < 0.001)) relative to prior expenditures and utilization without changing pre-existing trends. Much of this change was driven by 533 individuals initiating medication for the first time after cost-sharing removal. This initiation substantially increased average expenditure, especially for antiviral agents. Conclusions: Completely removing cost-sharing, independent of health status, significantly increased medication use and expenditure particularly due to medicine initiation by new users. While costs may be preventing use, the appropriateness of additional use, especially among new users, is unclear.